THE âŸ-COMPOSITION OF INTUITIONISTIC FUZZY IMPLICATIONS: AN ALGEBRAIC STUDY OF POWERS AND FAMILIES - SINGH, VISHNU; YADAV, SHIV PRASAD (International Journal of Mathematical Archive, 2018)
Viewing a binary operation âŸ between pair of fuzzy implications (FIs), the pair of nth powers of self FIs and the pair of a FI and its n th power proposed by Vemuri and Jayaram [15, 16, 17] is extended to the binary operation âŸ between pair of intuitionistic fuzzy implications (IFIs), the pair of n th powers of self IFIs and the pair of a IFI and its n th power. Finally, the basic properties like neutrality, ordering, exchange principles, the powers w.r.t. âŸ and their convergence, and the closures of some families of IFIs w.r.to the operation âŸ are studied.